Hi,
I have a similar problem similar to this one and my questions are:
As per Subhotosh Khan
"f(x) = A(x+2)(x-1)(x-3)(x-4) → f(0) = A * 2 * (-1) * (-3) *(-4) → 4 = A * (-24) → A = ?" Does A equal -1/6?
Therefore my equation to graph would be -1/6(x+2)(x-1)(x-3)(x-4) expanded to \(\displaystyle \, -\dfrac{x^4}{6}\, +\, x^3\, -\, \dfrac{x^2}{2}\, -\, \dfrac{13x}{3}\, +\, 4\)
Or am I missing something?
I have a similar problem similar to this one and my questions are:
As per Subhotosh Khan
"f(x) = A(x+2)(x-1)(x-3)(x-4) → f(0) = A * 2 * (-1) * (-3) *(-4) → 4 = A * (-24) → A = ?" Does A equal -1/6?
Therefore my equation to graph would be -1/6(x+2)(x-1)(x-3)(x-4) expanded to \(\displaystyle \, -\dfrac{x^4}{6}\, +\, x^3\, -\, \dfrac{x^2}{2}\, -\, \dfrac{13x}{3}\, +\, 4\)
Or am I missing something?
Last edited by a moderator: